Common polymorphism in H19 associated with birthweight and cord blood IGF-II levels in humans - Petry Clive J; Ong Ken K; Barratt Bryan J; Wingate Diane; Cordell Heather J; Ring Susan M; Pembrey Marcus E; Reik Wolf; Todd John A; Dunger David B (BMC Genetics, 2005)
Abstract Background Common genetic variation at genes that are imprinted and exclusively maternally expressed could explain the apparent maternal-specific inheritance of low birthweight reported in large family pedigrees. We identified ten single nucleotide polymorphisms (SNPs) in H19, and we genotyped three of these SNPs in families from the contemporary ALSPAC UK birth cohort (1,696 children, 822 mothers and 661 fathers) in order to explore associations with size at birth and cord blood IGF-II levels. Results Both offspring's and mother's H19 2992C>T SNP genotypes showed associations with offspring birthweight (P = 0.03 to P = 0.003) and mother's genotype was also associated with cord blood IGF-II levels (P = 0.0003 to P = 0.0001). The offspring genotype association with birthweight was independent of mother's genotype (P = 0.01 to P = 0.007). However, mother's untransmitted H19 2992T allele was also associated with larger birthweight (P = 0.04) and higher cord blood IGF-II levels (P = 0.002), suggesting a direct effect of mother's genotype on placental IGF-II expression and fetal growth. The association between mother's untransmitted allele and cord blood IGF-II levels was more apparent in offspring of first pregnancies than subsequent pregnancies (P-interaction = 0.03). Study of the independent Cambridge birth cohort with available DNA in mothers (N = 646) provided additional support for mother's H19 2992 genotype associations with birthweight (P = 0.04) and with mother's glucose levels (P = 0.01) in first pregnancies. Conclusion The common H19 2992T allele, in the mother or offspring or both, may confer reduced fetal growth restraint, as indicated by associations with larger offspring birth size, higher cord blood IGF-II levels, and lower compensatory early postnatal catch-up weight gain, that are more evident among mother's smaller first-born infants.